"Easy" and "hard" issues: Attitude extremity and a role of the need to evaluate. (11th November 2021) - Lee, Heysung
Abstract: Background: This article addresses the topic of issue polarization among the mass public, focusing on the classic typology of "easy" and "hard" issues (Carmines and Stimson, 1980) and the influence of the individual‐level motivational variable, which is the need to evaluate. Objective: Carmines and Stimson (1980) suggest that issues are characterized by their "hardness, " the degree of how much issues are easy to understand and make political evaluations. This article contends that the NTE would positively relate to attitude extremity of "hard" issues, which require extensive motivations for political judgment but would not necessarily be associated with attitude extremity of "easy" issues, which do not require such motivations. Methods: In the analyses, four "easy" issues (abortion, same‐sex marriage, affirmative action, and gun control) and four "hard" issues (immigration, tax, health care, and climate change) were selected to compare the effects of the NTE on attitude extremity, based on previous literature. The data of 2016 American National Election Survey was used to test the hypotheses. Results: The analyses using the data of the 2016 American National Election Survey supported the hypotheses by showing that the need to evaluate was related to increased attitude extremity on all "hard" issues, whereas need to evaluate was not associated with extremity on "easy" issues except the issue of affirmative action. Conclusion: Need to evaluate is related to attitude extremity on "easy" and "hard" issues.